2015
DOI: 10.1155/2015/247357
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Date Flesh or Pits Extract Attenuates Liver Fibrosis via Suppression of Hepatic Stellate Cell Activation and Reduction of Inflammatory Cytokines, Transforming Growth Factor-β1 and Angiogenic Markers in Carbon Tetrachloride-Intoxicated Rats

Abstract: Previous data indicated the protective effect of date fruit extract on oxidative damage in rat liver. However, the hepatoprotective effects via other mechanisms have not been investigated. This study was performed to evaluate the antifibrotic effect of date flesh extract (DFE) or date pits extract (DPE) via inactivation of hepatic stellate cells (HSCs), reducing the levels of inflammatory, fibrotic and angiogenic markers. Coffee was used as reference hepatoprotective agent. Liver fibrosis was induced by inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 69 publications
3
27
0
Order By: Relevance
“…2,34,35) The increase in serum level of these markers indicates a loss of liver cell membrane integrity, which might be directly related to an increase in ROS CCl 4 -induced. 36,37) In our study, we observed an obvious increase in the levels of TG about 63 and 113% in acute and chronic model respectively and TC about 38% in chronic model, which is in accordance with previous reports. 19,38) Lipids are a heterogeneous group containing active metabolic substances that play an important role in the pathogenesis of liver disease.…”
Section: Discussionsupporting
confidence: 93%
“…2,34,35) The increase in serum level of these markers indicates a loss of liver cell membrane integrity, which might be directly related to an increase in ROS CCl 4 -induced. 36,37) In our study, we observed an obvious increase in the levels of TG about 63 and 113% in acute and chronic model respectively and TC about 38% in chronic model, which is in accordance with previous reports. 19,38) Lipids are a heterogeneous group containing active metabolic substances that play an important role in the pathogenesis of liver disease.…”
Section: Discussionsupporting
confidence: 93%
“…Because the elevation of urea and creatinine is an indicator of renal disease, this indicates that DSP does not interfere with renal function. Additionally, intracellular enzymes, including ALT, AST, ALP, GGT and LDH, which are indicators of tissue injury, especially the liver for ALT, AST and ALP, (Al-Rasheed et al, 2015;Drent et al, 1996) were considered. An increase of these parameters has been related to hepatic, pancreatic and skeletal muscle diseases (Gowda et al, 2009).…”
Section: Stevensmentioning
confidence: 99%
“…Following liver injury, HSCs, which are dormant with low mitotic activity under basal conditions, are activated and change to myofibroblast-like cells, the chief producer of ECM protein in the liver, and increase their expression of α-SMA, which is a hallmark of activated HSCs [3]. Activated HSCs secrete TGF-β1 and CTGF to achieve their auto-activation [18].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Xi et al [28] suggested that inflammation-associated angiogenesis could contribute to progressive liver fibrosis. Furthermore, Al-Rasheed et al [3] proposed that an immature vascular plexus appeared around regenerating hepatocytes, impeded the exchange of oxygen and nutrients between sinusoids and hepatocytes, decreased parenchymal perfusion, and finally induced the progression of fibrosis.…”
Section: Discussionmentioning
confidence: 99%